Centralism and Local Government in Medieval England: Constitutional History and Assembly Politics, 950–1300 - Karn, Nicholas (History compass, 2012)
There is an extensive literature on English government in the middle ages, but its usefulness is limited by the terms in which it has been written, and its very partial coverage of the ways in which England was governed; these shortcomings are largely due to the origins of this historiography in the constitutional history written in the 19th century. As such, much of the historiography is overly concerned with the central institutions which directly served the kings, and tends to conceive of government in terms of institutions and bureaucratic relationships. The latter does not much correspond to the shakier realities of medieval government. The assumptions of constitutional history have been questioned in recent debate by those who suggest that assembly politics may be a better means of describing the working of medieval government.